Design of Wind Speed and Direction Sensor Based on Ultrasonic Phase Comparison Method - NIUHaodong; SHIYunbo; WANGTian; SHIQiheng (Journal of Harbin University of Science and Technology)
Aiming at the accurate identification of wind speed and direction in the natural environment, the wind speed and direction twoparameter sensor detection system was designed by ultrasonic principle The ultrasonic wave is generated in the system and the ultrasonic transducer with frequency 213kHz is used The ultrasonic sensor uses the ultrasonic phase difference method to measure the wind speed and direction The measurement principle and calculation method of the twodimensional phase difference method are elaborated The method is verified by Lissajous curve Feasibility Replacing complex analog circuits with the same digital chip in the system improves sensor integration The test results in the bellows show that the signal is processed by the phasedetection circuit and compared with ZRQF platinum resistance wire type wind speed sensor to verify the processing speed and accuracy The designed ultrasonic wind speed and direction test system in the gas flow direction detection and environment monitoring and other aspects have practical and effective detection and environmental monitoring